Korelasi Dukungan Keluarga dan Ketaatan terhadap Terapi Obat pada Individu dengan Diabetes Melitus Tipe 2 - Didan Prama Danutirta; Dwi Hendriani; Yona Palin T; Sutrisno Sutrisno (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Type 2 diabetes mellitus is a metabolic condition characterized by persistently high blood glucose levels due to impaired insulin production, resistance to insulin action, or a combination of both factors. Emotional support from individuals closely connected to patients plays a vital role in strengthening psychological resilience. Open communication with family allows patients to receive support in managing nutrition, reminders for medication adherence, and moral encouragement during times of fatigue or emotional distress. This study employed a cross-sectional design involving 55 respondents selected through simple random sampling, ensuring equal opportunity for participation. Data analysis was conducted using the chi-square test to assess the relationship between variables. The results showed a statistically significant association between family support and medication adherence (p < 0.000; α = 0.05). These findings underscore the importance of family involvement in improving treatment compliance among patients with Type 2 Diabetes Mellitus. It is hoped that patients will be more open to accepting family support and fostering effective communication. Family involvement should include emotional reinforcement, consistent reminders to take medications, and the sharing of relevant information about dietary restrictions or lifestyle adjustments. Strengthening this supportive relationship can enhance motivation, improve adherence to pharmacological regimens, and ultimately contribute to better disease management outcomes.